Importância do casqueamento e ferrageamento no cavalo atleta - Tridente, Márcia Franco [UNESP] (2011)
The trimming and shoeing are of great significance in the performance and longevity of the athlete horse, and if not done or done incorrectly, cause a variety of limb injuries, which may make unusable the animal for sport, a fact of frequent occurrence, due to the small number of trained professionals in this area. The anatomy of the hoof and its functions should be maintained by maintaining the balance of the same (correct hoof trimming) and, if necessary, proper shoeing, all to avoid the hull balance alterations that lead to osteoarthritis, musculoskeletal disorders, chronic pain at the bead, synovitis, pedal osteitis, navicular disease, in addition to increase tension in the flexor tendons, suspensory ligament and proximal sesamoid causing tendinitis, desmitis and sesamoiditis proximal